Teaching Prepositions in Surah Ar-Rahman: Analysis and Effective Teaching Methods - Muhammad Qadhafi; Aliyatul Jannah; Azmi Ali Muchtar (Al-Muyassar: Journal of Arabic Education, 2026)
This research aims to identify the prepositions in the Arabic grammar and to know the meanings of the prepositions in Surat Al-Rahman. The prepositions, which are simple materials, are not distinguished from the rules of the Arabic language, and has an important role in Arabic grammar, whether in the texts of the Holy Quran or other sciences. Learning prepositions and their rules is important. This research is library research, and it collects all data related to the topic of discussion. After obtaining data and research materials from the library, the researcher collects and classifies all data and materials to suit the research interests. The results of this research are that in Surah Ar-Rahman there are 94 prepositions. Each preposition has many meanings that differ from one another depending on the context of the word. In Surah Ar-Rahman, the preposition "min" has the meaning of partiality, the meaning of initiation, the meaning of in, the meaning of emphasis, the meaning of substitution, the meaning of "an", and the meaning of causation. The preposition "Ba" has the meaning of attachment, transitivity, swearing, substitution, companionship, and superiority. The preposition "ila" has the meaning of ending, accompanying, and near. The preposition "an" has the meaning of "on", substitution, from, and far. The preposition "ala" has the meaning of "in", "with", and "from". The preposition "kaf" has the meaning of comparison and emphasis. The preposition "lam" has the meaning of clarification, strengthening, and exclamation. The preposition "rabbi" has the meanings of abundance and diminution. There are two appropriate methods for teaching Arabic grammar using prepositions, as Kamel Mahmoud explains in his article "Methods of Teaching Arabic Grammar," namely the syllogistic method and the inductive method. The syllogistic method involves moving thought from a general rule to a specific rule, or from the general to the specific, i.e., from the rule to examples. The inductive method involves moving thought to a general rule or from the specific to the general, i.e., from examples to the rule.